2012
DOI: 10.1111/j.1440-1843.2011.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of C‐reactive protein in parapneumonic effusions

Abstract: This study demonstrated the value of CRP(ser) for prediction of RPT in patients with PPE. Moreover, when used in combination with classical biomarkers, CRP levels may be a useful adjunct for decision-making in relation to treatment of patients with non-purulent PPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…Skouras and colleagues [23] used the biomarker CRP to evaluate its clinical utility as a predictor in parapneumonic effusions (PPE). It has been estimated that approximately 40% of CAP can be associated with a PPE, most of which are inconsequential [24].…”
Section: Predicting Complications Outcomes and Mortalitymentioning
confidence: 99%
“…Skouras and colleagues [23] used the biomarker CRP to evaluate its clinical utility as a predictor in parapneumonic effusions (PPE). It has been estimated that approximately 40% of CAP can be associated with a PPE, most of which are inconsequential [24].…”
Section: Predicting Complications Outcomes and Mortalitymentioning
confidence: 99%
“…Pleural CRP levels are reportedly higher in parapneumonic effusions than in other types of exudates [ 2 , 14 , 18 ]. Evaluation of the pleural CRP levels is a useful test for differentiating between complicated and uncomplicated parapneumonic effusions [ 9 , 17 ] and between acute and chronic inflammation [ 18 ]. Kapisyzi et al [ 14 ] observed that the sensitivity of pleural CRP levels was higher than serum CRP levels in distinguishing transudative effusions from exudative effusions as well as malignant effusions from benign effusions.…”
Section: Discussionmentioning
confidence: 99%
“…Porcel et al [ 9 ] found that CRP levels >10 mg/dL were associated with complicated parapneumonic effusion and were associated with the need for pleural effusion drainage. Moreover, the combination of classical biomarkers (pleural pH < 7.2, LDH > 100 IU/dL, and glucose < 60 mg/dL) improves the accuracy of detecting parapneumonic effusion [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 40% of patients hospitalized with pneumonia have an accompanying pleural effusion [2]. Morbidity and mortality are higher in patients with pneumonia and pleural effusion than in those without pleural effusion [3].…”
Section: Introductionmentioning
confidence: 99%